2004
DOI: 10.1097/01.ju.0000108125.96072.ff
|View full text |Cite
|
Sign up to set email alerts
|

Local Anesthesia Before Transrectal Ultrasound Guided Prostate Biopsy: Comparison of 2 Methods in a Prospective, Randomized Clinical Trial

Abstract: We are quite convinced of the necessity of local anesthesia to decrease pain during transrectal prostate ultrasound guided biopsy. Rectal administration of lidocaine gel is safe, simple and effective even when no difference regarding pain is noted vs lidocaine periprostatic infiltration during the biopsy procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 18 publications
1
32
0
1
Order By: Relevance
“…There were no severe complications that required hospitalization in any of the patients. Similarly, in several studies, it has been shown that the use of periprostatic blockage with an intrarectal gel is better than placebo (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Entonox, which is a gas anaesthetic material (50% nO and 50% O 2 mixture), is widely used in the UK during delivery, in minor procedures treating trauma, and in emergencies, because it provides short-term anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…There were no severe complications that required hospitalization in any of the patients. Similarly, in several studies, it has been shown that the use of periprostatic blockage with an intrarectal gel is better than placebo (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Entonox, which is a gas anaesthetic material (50% nO and 50% O 2 mixture), is widely used in the UK during delivery, in minor procedures treating trauma, and in emergencies, because it provides short-term anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Inal [40] No adverse events from LA injection. No significant difference in hematuria and hematochezia between LA and CT. Mallick [43] No difference (LA vs. CT) in hematuria (2% vs. 2%), hematospermia (1% vs. 1%). Vanni [55] No difference in hematuria and rectal bleeding between LA & CT. Nambirajan [44] No significant difference in hematuria (8.4% vs. 10.4%), rectal bleeding (8.4% vs. 6.3%), hematospermia (18.8% vs. 23%) and infection (8.3% vs. 10.4%) between groups (LA vs. CT).…”
Section: Intrarectal Lignocainementioning
confidence: 99%
“…Patients with a final pathological diagnosis of cancer may suffer less pain than those with benign pathological results. 43 Pre-biopsy anxiety is also thought to be an important factor for increased pain sensation. 42 Further research into these factors will enable urologists to tailor their pain relief regime for each individual patient undergoing prostate biopsy.…”
Section: Intrarectal Lignocainementioning
confidence: 99%
See 1 more Smart Citation
“…6 The use of lidocaine topical anesthetic as a single agent for ocular procedures has been reviewed in several studies. [7][8][9][10][11][12][13] Although considered an off-label use of lidocaine 2% (urogenital) jelly, many of these ophthalmic studies had positive findings.…”
mentioning
confidence: 99%